Managing geographic information systems - Obermeyer, Nancy J (Guilford Press, 1994)
This book adopted text and practical reference addresses all aspects of developing and using geographic information systems (GIS) within an organization. Coverage includes the role of the GIS professional, how geographic information fits into broader management information systems, the use of GIS in strategic planning, and ways to navigate the organizational processes that support or inhibit the success of GIS implementation. All chapters retained from the prior edition have been thoroughly updated to reflect significant technological, empirical, and conceptual advances, as well as the changing contexts of GIS use. New chapters discuss organizational politics, metadata, legal issues, and GIS ethics.